Parfor and training of basic education teachers: obstacles and potentialities - de Melo Ferreira, Adriano (2020)
As a proposal of teacher formation policy through collaboration between the Union and federal entities, the National Training Plan of Basic Education Teachers (Parfor) has been in existence for a decade. But its continuity was obstructed by the Decree nº 8.752/2016, with its courses still ongoing and research focused on it still being undertaken. The documents analyzed here - doctoral theses and the scientific report of a research group - point to a wealth of data, at times contradictory, which forces one to think out dialectically the reality of the courses offered within the scope of Parfor, while considering their negative aspects and their potentialities.